2023
DOI: 10.3390/ijerph20064869
|View full text |Cite
|
Sign up to set email alerts
|

Taking Charge: Social Support Dynamics among Older Adults and Their Significant Others in COVID-19 Vaccination and Mitigation Efforts

Abstract: Older people have been disproportionately affected by the COVID-19 pandemic and are often portrayed as passive victims of this global health crisis. However, older adults do take responsibility for their own health and that of others in large part through social network dynamics. The purpose of this study was to understand the processes whereby older adults’ social networks shape their own health behaviors, and vice versa, in the context of COVID-19 vaccination and other mitigation efforts. Qualitative data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Moreover, as participants gradually lost faith in the credibility of the media and authoritative sources that are often associated with mediated communication, they began to place greater trust in individuals within their personal networks, including their home care aides and service providers whom they share personal relationships with. Such a finding is consistent with past studies that identify social networks as a strong facilitator of vaccination decisions [26,27]. Echoing past research, community-based efforts can play a pivotal role in combating vaccine hesitancy through tailored, localized strategies that address the specific concerns and needs of different groups.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, as participants gradually lost faith in the credibility of the media and authoritative sources that are often associated with mediated communication, they began to place greater trust in individuals within their personal networks, including their home care aides and service providers whom they share personal relationships with. Such a finding is consistent with past studies that identify social networks as a strong facilitator of vaccination decisions [26,27]. Echoing past research, community-based efforts can play a pivotal role in combating vaccine hesitancy through tailored, localized strategies that address the specific concerns and needs of different groups.…”
Section: Discussionsupporting
confidence: 88%
“…More notably, this research also suggests the particular influence possessed by older adults' peers. In a different paper from this study [26], we explicitly explored extensively on how older adults themselves serve as health advocates and sources of support.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study, psychological inflexibility mediated the relationship between COVID-19 stress and psychological well-being ( Duckering, 2022 ). A study showed that health behaviors related to COVID-19 were influenced by social support, altruism, life experience, and cognitive factors ( Rezakhani Moghaddam et al, 2022 ; Brennan-Ing et al, 2023 ). These findings reveal that infectious diseases and pandemics can affect all aspects of people’s lives.…”
Section: Discussionmentioning
confidence: 99%